A101 ARPC1B-DEFICIENT B CELLS DISPLAY ABERRANT SPREADING BEHAVIOUR - Leung, G (J Can Assoc Gastroenterol, 2018)
BACKGROUND: ARPC1B-deficiency is a newly described genetic condition with an early age of onset and is clinically similar to Wiskott-Aldrich syndrome (WAS). Nearly all affected patients experience colitis that is eosinophilic in nature, and their immunological profiles show increased peripheral CD19(+) cells, IgE, IgA, and detectable auto-antibodies. ARPC1B is a member of the Arp2/3 actin nucleating complex, which is activated by WAS protein and is the rate-limiting step in branched actin polymerization. It is expressed by haematopoietic cells and is important for regulating a dynamic cytoskeleton for essential functions such as migration and intracellular transport. AIMS: There are currently no data addressing the loss of ARPC1B and its effect on B cell function specifically. We intend to characterize how ARPC1B deficiency affects B cell activation in vitro. METHODS: EBV-transformed lymphoblastoid (B cell) lines were generated from PBMCs derived from patients and their first-degree relatives. B cell receptor (BCR) internalization was assessed by flow cytometry. Cell spreading was activated by receptor cross-linking: B cells were added to anti-human IgG-coated chamber slides and allowed to spread (2–20 min), then fixed and stained with phalloidin which binds filamentous (F)-actin. Images were acquired and analysed in ImageJ. RESULTS: Our group identified three patients harbouring mutations in ARPC1B: one with a severe phenotype (Pat 1) accompanied by a homozygous 2 bp insertion (c.387_388insCT [L90fs]) resulting in truncation, and two brothers with mild (Pat 2)/very mild (Pat 3) phenotypes caused by 2 homozygous SNPs (c.434C>T [A105V]; c.832G>A [A238T]). In B cell lysates, immunoblots confirmed the loss of ARPC1B in Pat 1, and reduced protein in Pat 2/3 compared to controls; this pattern was inversely correlated with expression of its isoform, ARPC1A. Flow cytometric analysis of phalloidin-stained B cells showed significantly reduced F-actin in all affected patients, while BCR expression was higher (internalization was not affected). Interestingly, a small proportion of unstimulated B cells from Pat 1 spontaneously adhered to tissue culture-treated surfaces after 2 d. Moreover, spreading assays demonstrated that a higher number of B cells from Pat 1 stuck down with no effect on spreading area. Upon closer inspection, structured illumination microscopy of phalloidin-stained B cells revealed a divergent spreading phenotype, with fewer extensive protrusions in cells from Pat 1. CONCLUSIONS: B cells deficient in ARPC1B have an inherent defect affecting their activity in vivo, BCR expression, and spreading behaviour in vitro. Further characterization is warranted to define the mechanism underlying this phenotype and its implications in the development of early onset IBD. FUNDING AGENCIES: CAG, CIHRHelmsley Charitable Trust